Community Perceptions in the Management of Birth Certificates and Death Certificates in the Department of Population and Civil Registry of West Aceh Regency - Nurul Badria Ulfa; Ikhsan Ikhsan; Nodi Marefanda (Universitas Teuku Umar, 2021)
This study aims to determine how public perceptions are and the factors that influence community perceptions in the service of obtaining birth certificates and death certificates at the Department of Population and Civil Registry of West Aceh Regency. The method used in this research is quantitative with data sources from 81 respondents who administer birth certificates and death certificates directly at Disdukcapil and the analysis technique used is correlation testing. The results of the study were carried out by testing the correlation between perceptual indicators and service indicators, it was known from the 9 tested service indicators, which obtained a correlation only on education indicators with personal service indicators which had test results of -0.270> 0.181 with a sig value of 0.015 and other supporting attributes. with age has a test result of 0.211> 0.181 with a sig value of 0.059. Disdukcapil in community service is good, provides comfort for the community, services are quite friendly and polite in providing, officers are responsible for receiving and solving problems from the community, getting convenience in administering birth and death certificates. So that it can be said that the factors that influence the service for obtaining birth certificates and death certificates are education for personal services and age for other supporting attributes.